(untitled) - Lê, Văn Thanh (Hà Nội, 2014)
This book introduction to culture and inter - cultural communication, marking introductions, verbal communication, niverbal communication, frienships, family values, educational attitudes, cultural conficts, cultural adjusment.
Keywords: Intercultural communication,Study and teaching,Giao tiếp đa văn hoá; Học tập vàn giảng dạy